Early switch from run-in treatment with vemurafenib plus cobimetinib to atezolizumab after 3 months leads to rapid loss of tumour control in patients with advanced BRAFV600-positive melanoma: the ImmunoCobiVem phase 2 randomised trial - Livingstone, Elisabeth; Gogas, H.; Kandolf-Sekulovic, L.; Meier, F.; Eigentler, T. K.; Ziemer, M.; Terheyden, P. A. M.; Gesierich, A. H.; Herbst, R. A.; Kähler, K. C.; Ziogas, D. C.; Mijuskovic, Z.; et al. (European journal of cancer, 2023)
Aim - ImmunoCobiVem investigated whether a planned switch to atezolizumab after achieving tumour control during run-in with vemurafenib + cobimetinib improves progression-free survival (PFS) and overall survival (OS) compared to continuous targeted therapy (TT) in patients with previously untreated advanced BRAFV600-mutated melanoma. - Methods - In this multicenter phase 2 study, patients received vemurafenib plus cobimetinib. After 3months, patients without progressive disease (PD) were randomly assigned (1:1) to continue vemurafenib + cobimetinib (Arm A) or switch to atezolizumab (Arm B) until first documented PD (PD1). Primary outcome was PFS1 (time from start of run-in until PD1 or death). OS and safety were also assessed. - Results - Of 185 patients enroled between November 2016 and December 2019, 135 were randomly assigned after the run-in period (Arm A, n = 69; Arm B, n = 66). Median PFS1 was significantly longer in Arm A versus Arm B (13.9 versus 5.9months; hazard ratio [HR] 0.55; 95% confidence interval [CI], 0.37-0.84; PStratified=0.001). Median OS was not reached in either arm (HR 1.22; 95%CI, 0.69-2.16; PStratified=0.389); 2-year OS was higher in Arm B versus Arm A (67%; 95%CI, 53-78 versus 58%; 95%CI, 45-70). Grade 3/4 AEs occurred in 55% of patients in Arm A and 64% in Arm B; treatment-related AEs led to discontinuation of any drug in 7% and 9% of patients, respectively. - Conclusion - In patients with BRAFV600-mutated advanced melanoma who achieve tumour control with TT, early switch at 3months to atezolizumab led to rapid loss of tumour control but provided a numerical OS benefit at 2years compared with continued TT.